Perancangan Sistem Informasi Pelayanan Pembuatan Surat Menyurat Berbasis Web Pada Kantor Desa Saga - Sri Rahayu; Putri Rachmanda; Adisa Lahmania Putri (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2022)
This research focuses on the use of developing technology in the aspect of government which is expected to be useful in strengthening the community through improving information and services, as well as improving a more efficient arrangement. The purpose of this study is to create a web-based correspondence service system to make it easier for residents to write correspondence and reduce congestion in queuing, and accommodate community needs well, so a systematic system was built, namely a computerized information system. The Saga Village Office is the topic of this research, which still uses a manual approach in managing its population. Researchers used an approach with an interview and observation process which was analyzed by the PIECES technique used to test (Performance, Information, Economy, Control, Efficiency, Service). Based on the analysis conducted, this system is made on a webbased basis because it is considered more practical and can be used multiplatform. On this website, the public can submit a request for an online letter.